Measuring the Impact of Monetary and Fiscal Actions: A New Look at the Specification Problem - Lombra, Raymond E.; Torto, Raymond G. (The Review of Economics and Statistics, 1974)
Raymond E. Lombra, Raymond G. Torto, Measuring the Impact of Monetary and Fiscal Actions: A New Look at the Specification Problem, The Review of Economics and Statistics, Vol. 56, No. 1 (Feb., 1974), pp. 104-107